Understanding the Islam Hadhari and ethnic relations: a non-Muslim perspective - Gill, Sarjit S.; Kaur, Charanjit (Department of History Education, University of Education Indonesia, 2009)
This piece of writing highlights an analysis of the ethnic relations in Malaysia based on the Islam Hadhari concept which is mainly aimed at fostering the spirit of goodwill and peace in Malaysia society. The idea of Islam Hadhari has so far been believed to play an important role in the development of human capital as it emphasizes individual development, especially in the aspect of religion (spiritual). This idea is meant to increase the competitiveness and endurance level of an individual to a more progressive in terms of mind and behavior, especially in the face of globalization wave today. However, the implementation of Islam Hadhari still vague and needs some more efforts in order to strengthen the spiritual ties among ethnic communities in the Malaysian society. Three questions are proposed in this case, those are: are non-Muslims willing to accept Islam Hadhari openly in their lives? How are the response and support of non-Malay community toward this Islam Hadhari concept? What important steps need to be done by certain agencies as an effort to empower Islam Hadhari especially the interest and participation of non-Muslims? These three questions should be taken into consideration because they concern with problems which emphasize the relationship between Muslims and non-Muslims ethnics in Malaysia. Thus, the discussion will be based on the social reality that is through experience and observation in daily life of Malaysia society in general and non-Islam society in particular.